Using of innovative educational and traning methods in the professional training of social workers - Lidiia Tymkiv (Vasyl Stefanyk Precarpathian National University, 2017)
The article deals with the use of innovative methods of training professional values ofsocial workers. It has been shown, that the use of innovative technologies in the educationalprocess will enhance the mental and social activities of prospective specialists in the socialsphere and prepare them for independent decision-making consistent with the acquired values. Key words : innovative methods of training, role games, game situation of professionaldirection.